2015
DOI: 10.1021/acs.jafc.5b04069
|View full text |Cite
|
Sign up to set email alerts
|

Flavanones and Chromones from Salicornia herbacea Mitigate Septic Lethality via Restoration of Vascular Barrier Integrity

Abstract: Salicornia herbacea is an annual halophytic glasswort that has been employed as a culinary vegetable, salad, and traditional medicinal resource. Chemical investigation of the aerial parts of S. herbacea led to the isolation of two new (1, 2) and known (3) flavanones as well as a new nature-derived (4) and two known chromone derivatives (5, 6). These purified compounds were evaluated for their suppressive potentials against the release of high-mobility group box 1 protein (HMGB1), which has captured attention a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Salicornia herbacea L., also known as glasswort, is widely distributed in saline soil areas such as the seashore, foreshore, and salt lakes in Korea, Japan, Iran, the United States, and European countries. [1][2][3][4][5] As an herbal halophyte, S. herbacea has been used as a folk medicine in Asian countries for the treatment of constipation, diabetes, nephropathy, hepatitis, and diarrhea. 2,3,6 Multiple scholars have reported that S. herbacea exhibits multiple bioactive functionalities, including antioxidant, anticancer, anti-inammatory, osteoblastogenesis, antihyperglycemic, and anti-hyperlipidemic effects.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Salicornia herbacea L., also known as glasswort, is widely distributed in saline soil areas such as the seashore, foreshore, and salt lakes in Korea, Japan, Iran, the United States, and European countries. [1][2][3][4][5] As an herbal halophyte, S. herbacea has been used as a folk medicine in Asian countries for the treatment of constipation, diabetes, nephropathy, hepatitis, and diarrhea. 2,3,6 Multiple scholars have reported that S. herbacea exhibits multiple bioactive functionalities, including antioxidant, anticancer, anti-inammatory, osteoblastogenesis, antihyperglycemic, and anti-hyperlipidemic effects.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] As an herbal halophyte, S. herbacea has been used as a folk medicine in Asian countries for the treatment of constipation, diabetes, nephropathy, hepatitis, and diarrhea. 2,3,6 Multiple scholars have reported that S. herbacea exhibits multiple bioactive functionalities, including antioxidant, anticancer, anti-inammatory, osteoblastogenesis, antihyperglycemic, and anti-hyperlipidemic effects. [5][6][7][8][9][10][11][12][13][14] Recently, S. herbacea has been widely cultivated and processed in various forms as commercially available functional cosmetics, dietary supplements and medicines due to its proven health benets and marketing strengths.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…S. herbacea -derived caffeoylated quinic acids showed anti-HMGB1 activity which exerted protection towards vasculature (Tuan et al 2015a ). The purified flavanones and chromone derivatives from the plant suppressed the release of HMGB1 in mice models, barricading the animal intestine from septic shocks (Tuan et al 2015b ). Role of the phytochemicals in hyperpermeability modulation needs to be investigated further, to better utilize the halophyte in fight against septicemia.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, extracting the main molecular skeleton and modifying its structures, especially with groups with excellent pharmacological activity, can enhance the pharmacological activity of natural products. Flavonoids are widely present in secondary metabolites of plants and microorganisms and used as template structures for drug discovery due to their broad and diverse activities, such as antibacterial, antifungal, antiviral, antioxidant, antitumor, and anti-inflammatory (Figure ). The 4 H -chromen-4-one core obtained by simplification of flavonoids can be optimized and modified, and the rational design can enhance the pharmacological activities of chromones. For example, some chromone derivatives bearing dithiocarbamate, 1,3,4-thiadiazole/oxadiazole, amide, thioether, 1,2,4-triazole, and Schiff base fragments have been successfully constructed and evaluated as potentially novel antimicrobial agents (Figure ). ,− Based on the structural features mentioned above, we propose that introducing a lipophilic fragment of an aromatic conjugated system containing a sulfur unit into the C-3 position of chromone may provide novel flavonoids with potential biological activity.…”
Section: Introductionmentioning
confidence: 99%